Concordance of IHC, FISH and RT-PCR for EML4-ALK rearrangements - Teixidó, Cristina (Transl Lung Cancer Res, 2014)
The echinoderm microtubule-associated protein-like 4 anaplastic lymphoma kinase (EML4-ALK) has emerged as the second most important driver oncogene in lung cancer and the first targetable fusion oncokinase to be identified in 4-6% of lung adenocarcinomas. Crizotinib, along with a diagnostic test—the Vysis ALK Break Apart fluorescence in situ hybridization (FISH) Probe Kit—is approved for the treatment of ALK positive advanced non-small cell lung cancer (NSCLC). However, the success of a targeted drug is critically dependent on a sensitive and specific screening assay to detect the molecular drug target. In our experience, reverse transcription polymerase chain reaction (RT-PCR)-based detection of EML4-ALK is a more sensitive and reliable approach compared to FISH and immunohistochemistry (IHC). Although ALK FISH is clinically validated, the assay can be technically challenging and other diagnostic modalities, including IHC and RT-PCR should be further explored.